Effects of forest certification towards sustainable community forestry in Nepal - Kandel, Pem N (Banko Janakari, 2007)
In early 2005, 10,045 ha Community Forests (CFs) were certified in Bajhang and Dolakha districts of Nepal by using the Forest Stewardship Council (FSC) certification scheme. After two years of forest certification, subsequent questions are being asked such as: What benefits have certification brought for the Forest Users Groups (FUGs)? What tangible differences are there in forest management system because of forest certification? and What lessons have been learnt from the certified forests? In an attempt to answer these questions, a study was carried out in April 2007 in Dolakha district where 11 (2,182 ha) community managed forests were certified in 2005. On the basis of field study from two certified forests (Vitteripakha and Suspa) of the district, this paper analyzes the effects of forest certification and its implications for enhancing Sustainable Community Forestry (SCF) in Nepal. Key words: Sustainable forest management, forest certification, community forestry Banko Janakari: A journal of forestry information for Nepal Vol.17(1) 2007 pp.11-16